2007
DOI: 10.1111/j.1467-9280.2007.01853.x
|View full text |Cite|
|
Sign up to set email alerts
|

Action-Video-Game Experience Alters the Spatial Resolution of Vision

Abstract: Playing action video games enhances several different aspects of visual processing; however, the mechanisms underlying this improvement remain unclear. Here we show that playing action video games can alter fundamental characteristics of the visual system, such as the spatial resolution of visual processing across the visual field. To determine the spatial resolution of visual processing, we measured the smallest distance a distractor could be from a target without compromising target identification. This appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
455
7
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 722 publications
(529 citation statements)
references
References 35 publications
19
455
7
24
Order By: Relevance
“…Playing these games can increase children's visual processing capacity in areas, which are components of the particular game. Such improved visual processing may have applications for rehabilitation (Green and Bavelier 2007).…”
Section: Visual and Motor Developmentmentioning
confidence: 99%
“…Playing these games can increase children's visual processing capacity in areas, which are components of the particular game. Such improved visual processing may have applications for rehabilitation (Green and Bavelier 2007).…”
Section: Visual and Motor Developmentmentioning
confidence: 99%
“…For example, Green and Bavelier [38] claimed that excessive playing video games can alter fundamental characteristics of the visual system, such as the spatial resolution of visual processing across the visual field. Swing [39] reported a positive correlation between video game experience and a composite index of symptoms related to attention deficits and hyperactivity.…”
Section: Present Researchmentioning
confidence: 99%
“…In humans, epidemiological studies have explored a wide number of factors that have been suggested to reduce age-related cognitive decline including both formal and informal education, leisure pursuits, intellectual engagement, physical fitness training, and expertise in different skill domains such as music, computer-game playing, language translation or meditation [75]. Playing computer games appears to improve certain aspects of visual attention such as spatial resolution and number of objects being tracked, which in turn could improve visual memory [48]. Perhaps the best established techniques for cognitive enhancement are healthy diet and physical exercise; several epidemiological studies have revealed significant correlations between physical exercise and cognition [27,124].…”
Section: Cognitive Trainingmentioning
confidence: 99%